PENINGKATAN KETRAMPILAN BERBAHASA INGGRIS BAGI MAHASISWA PKK DENGAN METODE PEMBELAJARAN LEARNER CENTERED - Dita Surwanti; Afria Dian Prastanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This research implemented learner-centered teaching methods in order to effectively improve studentsâ€Ÿ English language skills, specifically for PKK students in Sarjanawiyata Tamansiswa University. Learner-centered teaching methods are used to make students more active and provide students the opportunities to learn independently. These methods can increase studentsâ€Ÿ motivation to learn, deeper understanding, and more positive attitudes toward the subject being taught. The formulated research question in this research is â€œHow can learner-centered teaching methods improve PKK studentsâ€Ÿ English language skills?â€ Classroom action research is the chosen method to gather and analyze the data. The data was taken from 70 students of PKK students in the even semester from February till July 2016. Learner-centered teaching methods that were applied are creating procedural texts, conducting interviews in English and performing role plays in the class. These methods are effectively proven to improve studentsâ€Ÿ English language skills and turn students into autonomous learners.Keywords : Learner-centered teaching methods, action research.